Prevalence of Salmonella in broilers at retail outlets, processing plants and farms in Malaysia - Rahmat Ali, Gulam Rusul; Hashim, Jamal Khair; Radu, Son; Cheah, C. T.; Md. Yassin, R. (Elsevier Science, 1996)
A study was conducted to estimate the prevalence of Salmonella among broilers retailed at wet-markets and processing plants. Litter and feed samples obtained from both broiler and breeder farms were also examined for Salmonella. A total of 158 out of 445 (35.5%) and 52 out of 104 (50.0%) broiler carcasses obtained from wet-markets and processing plants were contaminated with Salmonella, respectively. Salmonella was isolated from 14 out of 98 (14.3%) samples of intestinal content. Litter samples from broiler and breeder farms were positive for Salmonella, 8/40 (20%) and 2/10 (20%), respectively. Salmonella isolates (230) belonging to 15 different serovars were isolated. Predominant serovars were S. enteritidis, S. muenchen, S. kentucky and S. blockley.